Decolonizing Luxury Fashion in Japan. (18th September 2020) - Slade, Toby
Abstract: Japan went from consuming more foreign luxury fashion brands than the rest of the world combined in the late 1980s to a complete rethinking of both the concept and practice of luxury after the bursting of its economic bubble. One key sensibility that arose was that of surōraifu, a Japanese word after the English "slow life." This esthetic, expressing the slowing down of time, was part of rising cultural nationalism but also represented a delinking of Japanese fashion from modernity/coloniality's horizon of expectations which positioned Europe as the font of desirable luxury consumption and European luxury fashion as a central symbol of civilization. This paper argues that in consumer culture Japan's modernity was colonial in defining the most valuable things as the goods from a foreign culture and that perspective changing crises are able to question the values and change the tastes of consumers in line with a decolonial delinking.